Solid waste management and the covid 19 pandemic lockdown in Zvishavane town, Zimbabwe - Jerie, S.; Musasa, T. (Bahir Dar University, 2023)
Management of solid waste is imperative towards public health especially when the globe has been struck by the deadly coronavirus pandemic. This paper examines the various categories of waste produced in the households in Zvishavane Municipality of Zimbabwe during the current Covid 19 epidemic. The study adopted the descriptive research design which allowed use of both quantitative and qualitative research techniques. In order to solicit data, a combination of field observations, document reviews, questionnaires and semi-structured interviews were used. In this study all the 50 waste pickers were selected to participate in the survey which implies that saturation sampling was adopted. Saturation sampling was adopted in this case since the total population did not exceed 100. The study revealed that the major types of waste generated in Zvishavane include food, glass, medical and wood waste. The study results demonstrate that a number of strategies such as waste prevention (50%), minimization (30%), reuse and recycling (40%) have been introduced to come up with a sustainable waste management structure in the mining town. The study concludes that good health and well-being which is part of the Sustainable Development Goals can only be achieved if solid waste management practices take place according to the approved sustainable waste management plans.